Gradient multi-layer composite wave-absorbing material with broadband absorption and preparation method of gradient multi-layer composite wave-absorbing material

By regulating the ratio of the absorbing function filler and the dielectric material, a multi-layer composite structure is designed layer by layer, which solves the problems of poor absorption efficiency and narrow bandwidth of traditional absorbing materials, and realizes the wide-frequency absorption characteristics and feasibility of industrial production.

CN119283397APending Publication Date: 2025-01-10CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311279070.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional single-layer absorbing materials have problems such as poor absorption efficiency and narrow absorption bandwidth, which is difficult to meet the market's demand for broadband absorption.

Method used

By regulating the type, coverage ratio and mass fraction of the wave absorbing function filler, a multi-layer composite structure design is adopted, and the layer by layer is poured and cured to form a reflective layer, microwave attenuation layer and an impedance matching layer, and the ratio of dielectric material and magnetic material is gradually formed. The layers are added to prepare a broad frequency absorption gradient multi-layer composite absorbing material.

Benefits of technology

It effectively broadens the effective absorption bandwidth of multi-layer composite absorbing materials, realizes ultra-wide frequency absorption characteristics, and is simple in process and easy to industrially produce, and meets the requirements of flexibility and broadband.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004477977690000111
    Figure BDA0004477977690000111
  • Figure HDA0004477977700000011
    Figure HDA0004477977700000011
  • Figure HDA0004477977700000012
    Figure HDA0004477977700000012
Patent Text Reader

Abstract

The invention provides a broadband wave-absorbing gradient multilayer composite wave-absorbing material and a preparation method thereof.According to the method, a 2D-0D dielectric-magnetic nanocomposite with a heterogeneous coating structure is selected as a functional filler and mixed with a silicone rubber matrix to prepare the broadband wave-absorbing gradient multilayer composite wave-absorbing material, and the concentration of the dielectric material is gradually increased from top to bottom; the invention relates to a gradient structure multilayer composite wave-absorbing material with gradually reduced magnetic material concentration. The effective wave-absorbing bandwidth of the multi-layer composite wave-absorbing material can be effectively widened by regulating and controlling the type, the coating ratio and the mass fraction of the wave-absorbing functional filler and the thickness of the multi-layer composite wave-absorbing material, and the gradient multi-layer composite material with the ultra-wideband absorption characteristic is achieved. Besides, according to the method provided by the invention, the flexible and weather-resistant silicone rubber material is used as a matrix, the multilayer composite wave-absorbing material is prepared in a layer-by-layer pouring and curing mode, the manufacturing process is simple, industrial production is easy, and commercial application with flexible and broadband requirements can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a gradient multilayer composite wave absorbing material with broadband absorption and a preparation method thereof. Background Art

[0002] With the rapid development of electronic communication technology, electromagnetic waves have gradually penetrated into all aspects of production and life, bringing great convenience to people's lives, but inevitably causing "electromagnetic pollution". Electromagnetic pollution not only affects the normal operation of electronic devices, but also endangers human health. However, traditional single-layer absorbing materials have the disadvantages of poor absorbing efficiency and narrow absorbing bandwidth, which makes it difficult to meet the market's requirements for strong absorbing ability and broadband absorption.

[0003] Structural absorbing materials have the advantages of integrated structure and function, light weight, and high absorption efficiency. Among structural materials, gradient multilayer impedance design has been proven to be an effective means to significantly improve the absorbing performance of electromagnetic absorbing materials. However, existing multilayer composite materials are difficult to process due to complex materials or structures, or the loss mechanism of absorbing functional fillers is single, resulting in poor improvement of effective absorbing bandwidth. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a gradient multilayer composite absorbing material with broadband absorption and a preparation method thereof. The method can effectively broaden the effective absorbing bandwidth of the multilayer composite absorbing material by regulating the type, coating ratio, mass fraction, and thickness of the multilayer composite absorbing material of the absorbing functional filler, thereby realizing a gradient multilayer composite material with ultra-broadband absorption characteristics.

[0005] The present invention provides a method for preparing a gradient multilayer composite absorbing material with broadband absorption, comprising the following steps:

[0006] Preparation of microwave absorbing functional fillers with different coating ratios;

[0007] The microwave absorbing functional fillers with different coating ratios are mixed with the silicone rubber matrix to obtain microwave absorbing slurries with different coating ratios;

[0008] The microwave absorbing slurries with different coating ratios are poured layer by layer, and cured layer by layer to obtain a gradient multilayer composite microwave absorbing material with broadband absorption;

[0009] The broadband absorption gradient multilayer composite absorbing material comprises a reflection layer, a microwave attenuation layer and an impedance matching layer; the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:(1-4)→1:(8-20)→1:(20-40).

[0010] Preferably, the magnetic material is selected from one or more of ferrite, magnetic alloy and magnetic metal element;

[0011] The dielectric material is selected from one or more of graphene, reduced graphene oxide, MXene, hexagonal boron nitride and transition metal sulfide.

[0012] In the present invention, the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:1→1:20→1:25;

[0013] Or the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:2→1:20→1:24;

[0014] Or the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:2→1:20→1:25;

[0015] Or the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:2→1:16→1:40.

[0016] Preferably, the mass ratio of the wave absorbing filler to the silicone rubber matrix is ​​100:20-500.

[0017] Preferably, the silicone rubber matrix comprises a mixture of vinyl-terminated silicone oil and a mixture of hydrogen-containing silicone oil in a mass ratio of 100:5-60;

[0018] The vinyl-terminated silicone oil mixture comprises vinyl-terminated silicone oil, a catalyst and an inhibitor in a mass ratio of (20-70):(0.3-10):(0.01-1);

[0019] The hydrogen-containing silicone oil mixture comprises hydrogen-containing silicone oil and a reinforcing agent in a mass ratio of (5-60):(5-60).

[0020] Preferably, the vinyl content of the vinyl-terminated silicone oil is 0.005 to 1.25 mmol / g, the molecular weight is 500 to 30000, and the viscosity at 25° C. is 10 to 3000 mPa·s;

[0021] The hydrogen content of the hydrogen-containing silicone oil is 0.20-16 mmol / g, the molecular weight is 100-20000, and the viscosity at 25° C. is 5-2000 mpa·s.

[0022] Preferably, the inhibitor is selected from one or more of ethynylcyclohexanol, 3,5-dimethyl-1-hexyn-3-ol and 3,6-dimethyl-l-heptyn-3-ol;

[0023] The reinforcing agent is selected from one or more of fumed silica, precipitated silica, quartz powder, zinc oxide, ferric oxide, titanium dioxide, zirconium silicate and calcium carbonate.

[0024] The present invention provides a broadband absorbing gradient multilayer composite wave absorbing material, which is prepared by the preparation method described in the above technical solution;

[0025] The gradient multilayer composite absorbing material comprises an impedance matching layer, a microwave attenuation layer and a reflection layer;

[0026] The raw materials for preparing the gradient multilayer composite absorbing material include absorbing functional fillers and a silicone rubber matrix;

[0027] The mass ratio of the wave absorbing functional material in the impedance matching layer, the wave absorbing functional material in the microwave attenuation layer and the wave absorbing functional material in the reflective layer is (20-70):(20-70):(20-70).

[0028] Preferably, the mass ratio of raw materials of magnetic material and dielectric material in the impedance matching layer is 100:2-50;

[0029] The mass ratio of the raw materials of the magnetic material and the dielectric material in the microwave attenuation layer is 100:5-50;

[0030] The mass ratio of the raw materials of the magnetic material and the dielectric material in the reflective layer is 100:10-100.

[0031] Preferably, the thickness ratio of the impedance matching layer, the microwave attenuation layer and the reflection layer is (0.1-3):(0.1-3):(0.1-3).

[0032] The present invention provides a method for preparing a gradient multilayer composite absorbing material with broadband wave absorption. The method selects a 2D-0D dielectric-magnetic nanocomposite material with a heterogeneous coating structure as a functional filler, and mixes it with a silicone rubber matrix to prepare a gradient structure multilayer composite absorbing material in which the concentration of the dielectric material gradually increases from top to bottom and the concentration of the magnetic material gradually decreases. By regulating the type of absorbing functional filler, the coating ratio, the mass fraction, and the thickness of the multilayer composite absorbing material, the effective absorbing bandwidth of the multilayer composite absorbing material can be effectively broadened, and a gradient multilayer composite material with ultra-broadband absorption characteristics is realized. In addition, the method provided by the present invention uses a flexible and weather-resistant silicone rubber material as a matrix, and prepares a multilayer composite absorbing material by pouring and curing layer by layer. The manufacturing process is simple, easy to industrialize, and can meet commercial applications with flexible and broadband requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic diagram of the structure of a broadband absorbing gradient multilayer composite absorbing material prepared by the present invention;

[0034] Figure 2 A curve diagram showing the relationship between the reflection loss of the composite absorbing material prepared in Example 1 of the present invention and the change in frequency;

[0035] Figure 3 A curve diagram showing the relationship between the reflection loss of the composite absorbing material prepared in Example 2 of the present invention and the change in frequency;

[0036] Figure 4 A curve diagram showing the relationship between the reflection loss of the composite absorbing material prepared in Example 3 of the present invention and the change in frequency;

[0037] Figure 5 A curve diagram showing the relationship between the reflection loss of the composite absorbing material prepared in Example 4 of the present invention and the change in frequency;

[0038] Figure 6 The graph is a relationship between the reflection loss of the composite absorbing materials prepared in Comparative Examples 1 to 5 of the present invention and the change in frequency. DETAILED DESCRIPTION

[0039] The present invention provides a method for preparing a gradient multilayer composite absorbing material with broadband absorption, comprising the following steps:

[0040] Preparation of microwave absorbing functional fillers with different coating ratios;

[0041] The microwave absorbing functional fillers with different coating ratios are mixed with the silicone rubber matrix to obtain microwave absorbing slurries with different coating ratios;

[0042] The microwave absorbing slurries with different coating ratios are poured layer by layer, and cured layer by layer to obtain a gradient multilayer composite microwave absorbing material with broadband absorption;

[0043] The broadband absorption gradient multilayer composite absorbing material comprises a reflection layer, a microwave attenuation layer and an impedance matching layer; the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:(1-4)→1:(8-20)→1:(20-40).

[0044] The present invention prepares absorbing functional fillers with different coating ratios. In the present invention, the magnetic material is selected from one or more of ferrite, magnetic alloy and magnetic metal element; the dielectric material is selected from one or more of graphene, reduced graphene oxide, MXene, hexagonal boron nitride and transition metal sulfide. The absorbing functional filler is a 2D-0D dielectric-magnetic nanocomposite material with a heterogeneous coating structure composed of 0D (0-dimensional) magnetic material and 2D (two-dimensional) dielectric material with a raw material weight ratio of 100:2 to 100. The absorbing functional filler enriches the electromagnetic wave loss mechanism and introduces a large number of heterogeneous interfaces, which greatly improves the electromagnetic wave attenuation ability of the gradient multilayer composite absorbing material. In a specific embodiment, the absorbing functional filler is GN@Ni, BN@CoNi, MXene@Fe3O4 or rGO@Fe3O4.

[0045] The magnetic material described in the present invention is prepared from a magnetic material precursor by a hydrothermal method, a solvothermal method or a thermal decomposition method; the magnetic material precursor is selected from one or more of an organic matter containing iron, an organic matter containing cobalt, an organic matter containing nickel, an inorganic matter containing iron, an inorganic matter containing cobalt and an inorganic matter containing nickel, preferably one or more of ferric acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, carbonyl iron, ferrous chloride and ferric chloride.

[0046] The dielectric material described in the present invention is prepared from a dielectric material precursor by a hydrothermal method, a solvent thermal method or a thermal decomposition method; the dielectric material precursor is selected from one or more of graphene oxide, Ti3AlC2, hexagonal boron nitride and transition metal sulfides.

[0047] The mass ratio of the precursors of the magnetic material and the dielectric material in the wave absorbing functional filler is 100:2-100; in a specific embodiment, the mass ratio of the precursors of the dielectric material and the magnetic material is 1:1; or 1:20; or 1:25; or 1:2; or 1:24; or 1:4; or 1:25; or 1:16. Specifically, the mass ratio of graphene oxide and iron acetylacetonate is 1:2, 1:20, and 1:24. Or the mass ratio of MXene and Fe(acac)3 is 1:2, 1:20, and 1:25. Or the mass ratio of hexagonal boron nitride, cobalt acetylacetonate and nickel acetylacetonate is 1:1:1, 1:8:8, and 1:20:20. Or the mass ratio of graphene (GN) and nickel acetylacetonate (Ni(acac)2 is 1:4, 1:20, and 1:24. In the specific embodiment of the present invention, three ratios of dielectric material and magnetic material precursors are set to prepare the wave absorbing functional filler.

[0048] The invention mixes wave-absorbing functional fillers with different coating ratios with a silicone rubber matrix to obtain wave-absorbing slurries with different coating ratios. The silicone rubber matrix comprises a vinyl-terminated silicone oil mixture and a hydrogen-containing silicone oil mixture in a mass ratio of 100:5-60.

[0049] The vinyl-terminated silicone oil mixture comprises a vinyl-terminated silicone oil, a catalyst and an inhibitor in a mass ratio of (20-70): (0.3-10): (0.01-1); the vinyl content of the vinyl-terminated silicone oil is 0.005-1.25 mmol / g, preferably 0.01-1.0 mmol / g, and more preferably 0.015-0.8 mmol / g; the molecular weight of the vinyl-terminated silicone oil is 500-30000, preferably 500-20000, and more preferably 600-18000; the viscosity of the vinyl-terminated silicone oil at 25°C is 10-3000 mpa·s, preferably 15-2500 mpa·s, and more preferably 15-2000 mpa·s. In a specific embodiment, the vinyl-terminated silicone oil is selected from a vinyl-terminated silicone oil with a vinyl content of 0.4 mmol / g, a viscosity of 150 mpa·s, and a molecular weight of 5000. The inhibitor is selected from one or more of ethynyl cyclohexanol, 3,5-dimethyl-1-hexyn-3-ol and 3,6-dimethyl-1-heptyn-3-ol; the catalyst is selected from one or more of chloroplatinic acid, Kaspersky catalyst and platinum catalyst.

[0050] The mass ratio of the vinyl-terminated silicone oil, the catalyst and the inhibitor is preferably (25-60):(0.5-5):(0.05-0.5); in a specific embodiment, the mass ratio of the vinyl-terminated silicone oil, the catalyst and the inhibitor is 60:4.5:0.5; or; in some embodiments, the weight proportion of the vinyl-terminated silicone oil is 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts or 60 parts, etc.; in some embodiments, the weight proportion of the catalyst is 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts or 5 parts, etc.; in some embodiments, the weight proportion of the inhibitor is 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts, etc.

[0051] The hydrogen-containing silicone oil mixture comprises hydrogen-containing silicone oil and a reinforcing agent in a mass ratio of (5-60):(5-60); the hydrogen content of the hydrogen-containing silicone oil is 0.20-16 mmol / g, preferably 0.30-15 mmol / g, and more preferably 0.4-10 mmol / g; the molecular weight of the hydrogen-containing silicone oil is 100-20000, preferably 200-17000, and more preferably 300-15000; the viscosity of the hydrogen-containing silicone oil at 25°C is 5-2000 mpa·s, preferably 10-1500 mpa·s, and more preferably 20-1200 mpa·s. In a specific embodiment, the hydrogen-containing silicone oil is selected from hydrogen-containing silicone oil with a hydrogen content of 1.2 mmol / g, a viscosity of 1000 mpa·s, and a molecular weight of 12000; or. The reinforcing agent is selected from one or more of fumed silica, precipitated silica, quartz powder, zinc oxide, ferric oxide, titanium dioxide, zirconium silicate and calcium carbonate.

[0052] The mass ratio of the hydrogen-containing silicone oil to the reinforcing agent in the hydrogen-containing silicone oil mixture is preferably (15-50): (15-50); in a specific embodiment, the mass ratio of the hydrogen-containing silicone oil to the reinforcing agent in the hydrogen-containing silicone oil mixture is 15:20; or 20:15. In some embodiments, the weight proportion of the hydrogen-containing silicone oil is 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts. In some embodiments, the weight proportion of the reinforcing agent is 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts.

[0053] In the present invention, the vinyl-terminated silicone oil, the inhibitor and the catalyst are preferably added to the stirring kettle for the first stirring to obtain a vinyl-terminated silicone oil mixture; the vinyl-terminated silicone oil mixture is preferably barreled and sealed for storage. In the present invention, the hydrogen-containing silicone oil and the reinforcing agent are added to the stirring kettle for the second stirring to obtain a hydrogen-containing silicone oil mixture, which is barreled and sealed for storage.

[0054] In the present invention, the mass ratio of the absorbing functional filler to the silicone rubber matrix is ​​100:20 to 500. In a specific embodiment, the mass ratio of the absorbing functional filler to the silicone rubber matrix in each layer of the gradient multilayer composite absorbing material is 45:55 or 40:60.

[0055] The present invention pours the absorbing slurry with different coating ratios layer by layer, and solidifies layer by layer to obtain a gradient multilayer composite absorbing material with broadband absorption. The present invention uses polytetrafluoroethylene or an iron frame structure of different thicknesses as a mold, pours the multiple absorbing slurries layer by layer into the mold cavity of the mold and solidifies them layer by layer. The curing temperature is 60 to 100°C, preferably 70 to 90°C; the curing time is 50 to 70 minutes, preferably 55 to 65 minutes. In a specific embodiment, the curing temperature is 80°C and the curing time is 60 minutes.

[0056] The present invention provides a broadband absorbing gradient multilayer composite wave absorbing material, which is prepared by the preparation method described in the above technical solution;

[0057] The gradient multilayer composite absorbing material comprises an impedance matching layer, a microwave attenuation layer and a reflection layer; the raw material ratio of the dielectric material and the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:(1-4)→1:(8-20)→1:(20-40);

[0058] The raw materials for preparing the gradient multilayer composite absorbing material include absorbing functional fillers and a silicone rubber matrix;

[0059] The mass ratio of the absorbing functional filler in the impedance matching layer, the absorbing functional filler in the microwave attenuation layer and the absorbing functional filler in the reflective layer is preferably (20-70): (20-70): (20-70). More preferably, the mass content of the absorbing functional filler in each layer is equal, except that the ratio of the dielectric material to the magnetic material in each layer is different.

[0060] See also Figure 1 , Figure 1 The schematic diagram of the structure of the broadband absorbing gradient multilayer composite absorbing material prepared by the present invention.

[0061] In the present invention, the mass ratio of raw materials of magnetic material and dielectric material in the impedance matching layer is 100:2-50;

[0062] The mass ratio of the raw materials of the magnetic material and the dielectric material in the microwave attenuation layer is 100:5-50;

[0063] The mass ratio of the raw materials of the magnetic material and the dielectric material in the reflective layer is 100:10-100.

[0064] The thickness ratio of the impedance matching layer, microwave attenuation layer and reflection layer in the present invention is (0.1-3):(0.1-3):(0.1-3); in a specific embodiment, the thickness ratio of the impedance matching layer, microwave attenuation layer and reflection layer is 1.89:0.66:1.0; or 2.41:1.36:0.5; or 2.07:1.96:0.8; or 1.81:1.48:1.0.

[0065] The gradient multilayer composite absorbing material provided by the present invention comprises an impedance matching layer, a microwave absorbing layer and a reflecting layer; wherein the impedance matching layer, the microwave absorbing layer and the reflecting layer are all composed of a 2D-0D dielectric-magnetic nanocomposite material with a heterogeneous coating structure and a silicone rubber matrix; the gradient multilayer composite absorbing material comprises a gradually increasing dielectric material concentration gradient and a gradually decreasing magnetic material concentration gradient from top to bottom. The multilayer structure design of the gradient structure can allow electromagnetic waves to enter the interior of the composite material to the maximum extent, thereby greatly broadening the microwave effective absorbing bandwidth of the absorbing composite material.

[0066] The present invention adopts the bow method (GJB 2038A-2011) to test the above-mentioned broadband absorption gradient multilayer composite absorbing material; the test size is 18cm*18cm.

[0067] In order to further illustrate the present invention, a broadband absorption gradient multilayer composite absorbing material and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0068] Example 1

[0069] 0.1g of graphene oxide and different masses of iron acetylacetonate (0.2g, 2.0g, 2.4g) were placed in a three-necked flask and dispersed in 25ml of triethylene glycol by ultrasonication for 30min. Under an argon atmosphere, the mixture was heated to 290°C at a heating rate of 3°C / min and refluxed for 30min. After the mixture was cooled to room temperature, the black precipitate was collected and washed repeatedly with ethyl acetate and ethanol three times. Finally, the product was dried at 60°C for 8 hours to obtain rGO@Fe3O4 nanocomposites with different coating ratios;

[0070] 60 parts of vinyl-terminated silicone oil (vinyl content of 0.4 mmol / g, viscosity of 150 mPa·s, molecular weight of 5000), 4.5 parts of platinum catalyst, and 0.5 parts of ethynyl cyclohexanol were put into a stirring kettle and stirred at room temperature for 1 hour to mix them evenly to obtain a vinyl-terminated silicone oil mixture.

[0071] 15 parts of hydrogen-containing silicone oil (hydrogen content 1.2 mmol / g, viscosity 1000 mpa·s, molecular weight 12000) and 20 parts of fumed silica reinforcing agent were put into a stirring kettle and stirred at room temperature for 1 hour to mix them evenly to obtain a hydrogen-containing silicone oil mixture.

[0072] 45 parts of rGO@Fe3O4 nanocomposites with different coating ratios, 27.5 parts of end-vinyl silicone oil mixture, and 27.5 parts of hydrogen silicone oil mixture were stirred at room temperature for 30 minutes, poured into a polytetrafluoroethylene frame mold of a certain thickness, cured at 80℃ for 1 hour, and cured layer by layer by layer casting to obtain three-layer rGO@Fe3O4 / silicone rubber composites with a raw material ratio of GO:Fe(acac)3=1:2, 1:20, 1:24 as the reflection layer, microwave attenuation layer and impedance matching layer, respectively, with corresponding thicknesses of 1.0mm, 0.66mm and 1.89mm. The bow method (GJB 2038A-2011) was used to test the sample with a size of 18cm*18cm, and it was found that the composite material showed an excellent minimum reflection loss value (-62.0dB) and an ultra-wide effective absorption bandwidth (9.28GHz) at 10GHz.

[0073] Example 2

[0074] 1.6 g lithium fluoride was slowly added to 20 ml 9 M hydrochloric acid solution, stirred at room temperature for 20 min, then 1.0 g Ti3AlC2 was slowly added, reacted at 35 ° C for 36 h, and then washed repeatedly with deionized water until the solution pH> 6 (centrifuged at 3500 r / min for 5 min), the lower layer of precipitate was collected, 100 ml of deionized water was added for ultrasonic treatment for 20 min, centrifuged at 3500 r / min for 60 min, the upper layer of liquid was collected, and few-layer MXene was obtained after freeze-drying;

[0075] 100 mg MXene and different masses of Fe(acac)3 (0.1 g, 2.0 g, 2.5 g) were placed in a three-necked flask and dispersed in 25 ml TEG by ultrasonication for 10 min. Under an argon atmosphere, the mixture was heated to 290 ° C at a heating rate of 3 ° C / min and refluxed for 30 min. After the mixture was cooled to room temperature, the black precipitate was collected and washed repeatedly with ethyl acetate and ethanol three times, and finally the product was dried at 60 ° C for 8 hours. MXene@Fe3O4 nanocomposites with different coating ratios were obtained;

[0076] 60 parts of vinyl-terminated silicone oil (vinyl content of 0.4 mmol / g, viscosity of 150 mPa·s, molecular weight of 5000), 4.5 parts of card catalyst, and 0.5 parts of ethynyl cyclohexanol were put into a stirring kettle and stirred at room temperature for 1 hour to mix them evenly to obtain a vinyl-terminated silicone oil mixture.

[0077] 20 parts of hydrogen-containing silicone oil (hydrogen content 1.2 mmol / g, viscosity 1000 mpa·s, molecular weight 12000) and 15 parts of fumed silica reinforcing agent were put into a stirring kettle and stirred at room temperature for 1 hour to mix them evenly to obtain a hydrogen-containing silicone oil mixture.

[0078] 40 parts of MXene@Fe3O4 nanocomposites with different coating ratios, 30 parts of vinyl-terminated silicone oil mixture, and 30 parts of hydrogen-containing silicone oil mixture were stirred at room temperature for 20 minutes, poured into a polytetrafluoroethylene frame mold of a certain thickness, cured at 80°C for 1 hour, and cured by pouring layer by layer. After curing, three-layer MXene@Fe3O4 / silicone rubber composites with a raw material ratio of MXene:Fe(acac)3=1:1, 1:20, and 1:25 were obtained, respectively, as the reflection layer, microwave attenuation layer, and impedance matching layer, and the corresponding thicknesses were 0.5mm, 1.36mm, and 2.41mm. The bow method (GJB 2038A-2011) was used to test the sample with a size of 18cm*18cm. It was found that the composite material showed an excellent minimum reflection loss value (-54.7dB) and an ultra-wide effective absorption bandwidth (9.92GHz) at 10GHz, and is an excellent candidate for microwave absorption materials.

[0079] Example 3

[0080] 0.1g of hexagonal boron nitride and different masses of cobalt acetylacetonate (Co(acac)2, 0.1g, 0.8g, 2.0g) and nickel acetylacetonate (Ni(acac)2, 0.1g, 0.8g, 2.0g) were placed in a three-necked flask, 50ml of oleylamine and 50ml of dibenzyl ether were added, and ultrasonication was performed for 30 minutes to completely disperse them. In an argon atmosphere, the mixture was kept at 100°C for 1h, then the temperature was rapidly increased to 300°C at a heating rate of 10°C / min, and refluxed for 30min. After the mixture was cooled to room temperature, the black precipitate was collected, washed repeatedly with petroleum ether and ethanol three times, and finally the product was dried at 60°C for 8 hours. BN@CoNi nanocomposites with different coating ratios were obtained;

[0081] 60 parts of vinyl-terminated silicone oil (vinyl content of 0.4 mmol / g, viscosity of 150 mPa·s, molecular weight of 5000), 4.5 parts of platinum catalyst, and 0.5 parts of ethynyl cyclohexanol were put into a stirring kettle and stirred at room temperature for 1 hour to mix them evenly to obtain a vinyl-terminated silicone oil mixture.

[0082] 15 parts of hydrogen-containing silicone oil (hydrogen content 1.2 mmol / g, viscosity 1000 mpa·s, molecular weight 12000) and 20 parts of fumed silica reinforcing agent were put into a stirring kettle and stirred at room temperature for 1 hour to mix them evenly to obtain a hydrogen-containing silicone oil mixture.

[0083] 55 parts of BN@CoNi nanocomposites with different coating ratios, 22.5 parts of end-vinyl silicone oil mixture, and 22.5 parts of hydrogenated silicone oil mixture were stirred at room temperature for 30 minutes, poured into a polytetrafluoroethylene frame mold of a certain thickness, cured at 80°C for 1 hour, and cured layer by layer by layer casting to obtain three-layer BN@CoNi / silicone rubber composites with a raw material ratio of BN: Co(acac)2: Ni(acac)2 = 1:1:1, 1:8:8, 1:20:20 as the reflection layer, microwave attenuation layer and impedance matching layer, respectively, with corresponding thicknesses of 0.8mm, 1.96mm and 2.07mm. The bow method (GJB 2038A-2011) was used to test the sample with a size of 18cm*18cm, and it was found that the composite material showed an excellent minimum reflection loss value (-60.8dB) and an ultra-wide effective absorption bandwidth (8.46GHz) at 12GHz.

[0084] Example 4

[0085] 0.1g of graphene (GN) and different masses of nickel acetylacetonate (Ni(acac)2, 0.4g, 2.0g, 2.4g) were placed in a three-necked flask and dispersed in 100ml of 2-pyrrolidone by ultrasound for 30min. 5g of octadecylamine was added to the above solution and heated to 120°C for 30 minutes. Subsequently, the temperature of the reaction system was increased to 245°C to induce boiling of 2-pyrrolidone, and the reaction was maintained for 2 hours by stirring and reflux under nitrogen protection. Finally, 100ml of ethanol was injected into the reaction system to rapidly reduce the reaction temperature and stop the reaction. After centrifugal separation, the mixture was washed alternately with n-hexane and acetone for several times and dried in vacuo at 40°C. GN@Ni nanocomposites with different coating ratios were obtained;

[0086] 60 parts of vinyl-terminated silicone oil (vinyl content of 0.4 mmol / g, viscosity of 150 mPa·s, molecular weight of 5000), 4.5 parts of platinum catalyst, and 0.5 parts of ethynyl cyclohexanol were put into a stirring kettle and stirred at room temperature for 1 hour to mix them evenly to obtain a vinyl-terminated silicone oil mixture.

[0087] 15 parts of hydrogen-containing silicone oil (hydrogen content 1.2 mmol / g, viscosity 1000 mpa·s, molecular weight 12000) and 20 parts of fumed silica reinforcing agent were put into a stirring kettle and stirred at room temperature for 1 hour to mix them evenly to obtain a hydrogen-containing silicone oil mixture.

[0088] 40 parts of GN@Ni nanocomposites with different coating ratios, 30 parts of end-vinyl silicone oil mixture, and 30 parts of hydrogenated silicone oil mixture were stirred at room temperature for 30 minutes, and the mixture was poured into a polytetrafluoroethylene frame mold of a certain thickness, cured at 80°C for 1 hour, and cured layer by layer by layer casting to obtain a three-layer GN@Ni / silicone rubber composite material with a raw material ratio of GO:Ni(acac)2=1:4, 1:20, and 1:24 as the reflection layer, microwave attenuation layer, and impedance matching layer, respectively, with corresponding thicknesses of 1.0mm, 1.48mm, and 1.81mm. The bow method (GJB 2038A-2011) was used to test the sample with a size of 18cm*18cm, and it was found that the composite material showed an excellent minimum reflection loss value (-54.7dB) and an ultra-wide effective absorption bandwidth (7.28GHz) at 12GHz.

[0089] Comparative Examples 1 to 5

[0090] The experimental conditions of Example 1 are used as the reference, and the differences are shown in Table 1:

[0091] The present invention prepares the multilayer composite materials of Comparative Examples 1 to 5 according to the preparation process and the selection of each component of Examples 1 to 4, wherein the raw material ratio and thickness of each layer and the performance of the multilayer absorbing material are shown in Table 1:

[0092] Table 1 Raw material ratio and performance test results of comparative examples 1 to 5

[0093]

[0094] As can be seen from the above embodiments, the present invention provides a method for preparing a gradient multilayer composite absorbing material with broadband wave absorption. The method selects a 2D-0D dielectric-magnetic nanocomposite material with a heterogeneous coating structure as a functional filler, and mixes it with a silicone rubber matrix to prepare a gradient structure multilayer composite absorbing material in which the concentration of the dielectric material gradually increases from top to bottom and the concentration of the magnetic material gradually decreases. By regulating the type of absorbing functional filler, the coating ratio, the mass fraction, and the thickness of the multilayer composite absorbing material, the effective absorbing bandwidth of the multilayer composite absorbing material can be effectively broadened, and a gradient multilayer composite material with ultra-broadband absorption characteristics is realized. In addition, the method provided by the present invention uses a flexible and weather-resistant silicone rubber material as a matrix, and prepares a multilayer composite absorbing material by pouring and curing layer by layer. The manufacturing process is simple, easy to industrialize, and can meet commercial applications with flexible and broadband requirements. The experimental results show that at 10GHz, the minimum reflection loss value of the gradient multilayer composite absorbing material is -62.0~-54.7dB, and the effective absorption bandwidth is 9.28~9.92GHz; at 12GHz, the minimum reflection loss value of the gradient multilayer composite absorbing material is -54.7~-60.8dB, and the effective absorption bandwidth is 7.28~8.46GHz.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a gradient multilayer composite absorbing material with broadband absorption, comprising the following steps: Preparation of microwave absorbing functional fillers with different coating ratios; The microwave absorbing functional fillers with different coating ratios are mixed with the silicone rubber matrix to obtain microwave absorbing slurries with different coating ratios; The microwave absorbing slurries with different coating ratios are poured layer by layer, and cured layer by layer to obtain a gradient multilayer composite microwave absorbing material with broadband absorption; The broadband absorption gradient multilayer composite absorbing material comprises a reflection layer, a microwave attenuation layer and an impedance matching layer; the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:(1-4)→1:(8-20)→1:(20-40).

2. The preparation method according to claim 1, characterized in that: The magnetic material is selected from one or more of ferrite, magnetic alloy and magnetic metal element; The dielectric material is selected from one or more of graphene, reduced graphene oxide, MXene, hexagonal boron nitride and transition metal sulfide.

3. The preparation method according to claim 1, characterized in that: The raw material ratio of the dielectric material and the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:1→1:20→1:25; Or the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:2→1:20→1:24; Or the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:2→1:20→1:25; Or the raw material ratio of the dielectric material to the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:2→1:16→1:

40.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the wave absorbing functional filler to the silicone rubber matrix is ​​100:20-500.

5. The preparation method according to claim 1, characterized in that: The silicone rubber matrix comprises a mixture of vinyl-terminated silicone oil and a mixture of hydrogen-containing silicone oil in a mass ratio of 100:5-60; The vinyl-terminated silicone oil mixture comprises vinyl-terminated silicone oil, a catalyst and an inhibitor in a mass ratio of (20-70):(0.3-10):(0.01-1); The hydrogen-containing silicone oil mixture comprises hydrogen-containing silicone oil and a reinforcing agent in a mass ratio of (5-60):(5-60).

6. The preparation method according to claim 5, characterized in that: The vinyl content of the vinyl-terminated silicone oil is 0.005 to 1.25 mmol / g, the molecular weight is 500 to 30000, and the viscosity at 25° C. is 10 to 3000 mpa·s; The hydrogen content of the hydrogen-containing silicone oil is 0.20-16 mmol / g, the molecular weight is 100-20000, and the viscosity at 25° C. is 5-2000 mpa·s.

7. The preparation method according to claim 5, characterized in that: The inhibitor is selected from one or more of ethynylcyclohexanol, 3,5-dimethyl-1-hexyn-3-ol and 3,6-dimethyl-l-heptyn-3-ol; The reinforcing agent is selected from one or more of fumed silica, precipitated silica, quartz powder, zinc oxide, ferric oxide, titanium dioxide, zirconium silicate and calcium carbonate.

8. A gradient multilayer composite absorbing material with broadband absorption, prepared by the preparation method according to any one of claims 1 to 7; The gradient multilayer composite absorbing material comprises an impedance matching layer, a microwave attenuation layer and a reflection layer; the raw material ratio of the dielectric material and the magnetic material in the reflection layer, the microwave attenuation layer and the impedance matching layer increases layer by layer from 1:(1-4)→1:(8-20)→1:(20-40); The raw materials for preparing the gradient multilayer composite wave-absorbing material include wave-absorbing functional fillers and a silicone rubber matrix.

9. The broadband absorption gradient multilayer composite absorbing material according to claim 8, characterized in that: The mass ratio of the raw materials of the magnetic material and the dielectric material in the impedance matching layer is 100:2-50; The mass ratio of the raw materials of the magnetic material and the dielectric material in the microwave attenuation layer is 100:5-50; The mass ratio of the raw materials of the magnetic material and the dielectric material in the reflective layer is 100:10-100.

10. The broadband absorption gradient multilayer composite absorbing material according to claim 8, characterized in that: The thickness ratio of the impedance matching layer, the microwave attenuation layer and the reflection layer is (0.1-3):(0.1-3):(0.1-3).

Citation Information

Cited By

  • Preparation method of melt-blown cloth flexible wave-absorbing material

    CN122304177A